Adolescent Chronic Health Conditions and School Disconnectedness. Issue 2 (February 2022) - James, Christine; Corman, Hope; Noonan, Kelly; Reichman, Nancy E.; Jimenez, Manuel E.
Abstract: Objective: The objective of this study was to examine associations between chronic health conditions and school disconnectedness, trouble getting along with others at school, and peer victimization at age 15. Method: We conducted a secondary analysis of population-based data from the Fragile Families and Child Wellbeing birth cohort to investigate associations between chronic developmental/behavioral and physical health conditions and school disconnectedness, trouble getting along with others at school, and peer victimization of adolescents using mother-reported child health conditions and youth-reported relationships/experiences at school ascertained from standardized scales. Associations were examined using linear and logistic regression models adjusting for confounding factors. Results: Of the 2874 adolescents included, more than one-third had at least 1 chronic health condition. Compared with those with no chronic health conditions, adolescents with developmental/behavioral health conditions felt more disconnected from school (by 0.22 SDs), had more trouble getting along with others at school (0.22 SD), and were more victimized by peers at school (0.20 SD). Teens with physical health conditions also felt more disconnected from school (0.10 SD), had more trouble getting along with others at school (0.12 SD), and were more victimized by peers (0.12 SD). One noteworthy difference was that adolescents with developmental/behavioral conditions were more likely than those with no conditions to report trouble getting along with teachers, but adolescents with physical health conditions were not. Conclusion: Chronic health conditions were associated with disconnectedness from school and negative school social interactions in this study of US urban youth, suggesting that targeted resources and interventions for this population are needed. Abstract : This article has supplementary material on the web site: www.jdbp.org.